Application of artificial intelligence algorithms in pediatric dermatology. - Sokolov, K.; Shpudeiko, V.; Koval, M.; Sidaruk, H. (European Journal of Pediatric Dermatology, 2023)
Modern information technology makes it possible to change the classical approach to the diagnosis and treatment of dermatological diseases in children. Artificial intelligence (AI) algorithms are becoming reliable assistants for pediatricians in the diagnosis of skin diseases. In turn, this makes it possible to increase the detection of early forms of dermatological disorders, to correctly allocate patients at the primary stage of medical care, or to exclude unjustified referrals to other specialists altogether. Given these prospects, many countries around the world are already adopting strategic plans to introduce such tools into medical practice.